Career Opportunities of Social Science Students from a Growth Mindset Perspective through the Utilization of Digital Career Guidance Media - Monica, Mega Aria; Reiska Primanisa; Paksi Tri Nugraha (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze career opportunities of Social Science (IPS) students from a growth mindset perspective through the utilization of digital career guidance media. The main problem addressed in this study is the low level of students’ self-understanding, limited access to career information, and negative stigma toward IPS majors, which affects their career readiness. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects were eleventh-grade students in Bandar Lampung. The instruments included expert validation questionnaires, student response questionnaires, and effectiveness tests. The results indicate that the digital career guidance media has a high feasibility level (≥85%) and received positive responses from 98.8% of students. Furthermore, there was a significant improvement in students’ career understanding and readiness. The integration of growth mindset successfully transformed students’ perceptions of career opportunities into more adaptive and open perspectives. This study contributes to the development of digital-based career guidance services that are not only informative but also transformative.